Practical precooling: Effect on cycling time trial performance in warm conditions - Quod, M. J.; Martin, D. T.; Laursen, P. B.; Gardner, A. S.; Halson, S. L.; Marino, F. E.; Tate, M. P.; Mainwaring, D. E.; Gore, C. J.; Hahn, A. G. (Journal of Sports Sciences, 2008)
The purpose of this study was to compare the effects of two practical precooling techniques (skin cooling vs. skin + core cooling) on cycling time trial performance in warm conditions. Six trained cyclists completed one maximal graded exercise test (VO2peak 71.4 ± 3.2 ml/kg·min) and four ~40 min laboratory cycling time trials in a heat chamber (34.3°C ± 1.1°C; 41.2% ± 3.0% rh) using a fixed-power/variable-power format. Cyclists prepared for the time trial using three techniques administered in a randomised order prior to the warm-up: (1) no cooling (control), (2) cooling jacket for 40 min (jacket) or (3) 30-min water immersion followed by a cooling jacket application for 40 min (combined). Rectal temperature prior to the time trial was 37.8°C ± 0.1°C in control, similar in jacket (37.8°C ± 0.3°C) and lower in combined (37.1°C ± 0.2°C, P < 0.01). Compared with the control trial, time trial performance was not different for jacket precooling (-16 ± 36 s, -0.7%; P = 0.35) but was faster for combined precooling (-42 ± 25 s, -1.8%; P = 0.009). In conclusion, a practical combined precooling strategy that involves immersion in cool water followed by the use of a cooling jacket can produce decrease in rectal temperature that persist throughout a warm-up and improve laboratory cycling time trial performance in warm conditions.